Strategi Pelayanan Prima Dalam Menumbuhkan Kepercayaan Jamaah Umrah Pada PT. Wisata Titian Nusantara Pelangi - Ferry Setyadi Atmadja; Sugiharto Sugiharto (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2019)
The purpose of this study is to examine the success of PT. Titiannusantara PelangiTourism in excellent service by explaining strategies in implementing excellent service and implementing excellent services that can foster the trust of Umrah pilgrims and describe the condition of the company through a SWOT analysis. This research uses a qualitative methodology with descriptive analysis techniques. The data obtained from the institution is then processed systematically in the form of written words, archives and oral, as well as the observed behavior to obtain information related to the prime service strategy in growing the trust of Umrah pilgrims.